Fixed drug eruption – pathogenesis and diversity of clinical manifestations - Tekely, Emilia; Kądziela-Wypyska, Grażyna; Chodorowska, Grażyna (Dermatology Review/Przegląd Dermatologiczny, 2012)
Fixed drug eruption (FDE) is a distinctive type of drug-induced cutaneous reactions characterized by recurrence at the same site of the skin or mucous membrane after exposure to the responsible agent. Erythematous-oedematous macules appearing after drug exposure are present for several days, and disappear with residual hyperpigmentation. Various groups of drugs, including H1-antihistaminic, can be the cause of FDE, but offending agents vary from country to country. Moreover, cross-reactions may occur with structurally similar drugs. Although the exact pathogenesis remains not sufficiently elucidated, cell-mediated cytotoxic reaction against the epidermal keratinocytes is strongly suggested. Epidermal CD8+ memory T cells present in lesional skin are believed to contribute to immunological memory, being reactivated on re-challenge. This review presents the current knowledge on the role of the cell-mediated immune response in the pathogenesis of fixed drug eruption, and clinical variants and management are also discussed.